Evaluation of In vitro and In vivo Antioxidant potential of Morinda reticulata Gamble Tubers in Wistar Albino Rats Subjected to CCl4 and Paracetamol induced Hepatotoxicity - Asirvatham, Raju; Usha, Joshila Jose (INDONESIAN JOURNAL OF PHARMACY, 2017)
The aim of present study is to explore the antioxidant potential of ethanol and aqueous extracts of Morinda reticulata Gamble by in vitro and in vivo methods. Â In vitro antioxidant activity of Benzene, Chloroform, Ethanol and aqueous extracts of Â M. reticulata was studied by DPPH, Metal chelating, Super oxide free radical scavenging assay, Hydroxyl radical scavenging assay and Reducing power assay where ascorbic acid was used as a standard antioxidant. Oxidative stress in Wistar rats was induced by two different models using administration of CCl4 (1.5 ml/kg, p.o) and paracetamol (2g/kg) on seventh day of study. Ethanol and aqueous extracts were given twice daily for one week. Silymarin (25 mg/kg, p.o) was given as a standard drug. In in vitro, IC50 values were least with ethanol and aqueous extracts when compared with other extracts. Ethanol extracts exhibited similar free radical scavenging effect as that of standard ascorbic acid.Â  In vivo antioxidant activity was assessed by the measurement of Melondyaldehyde (MDA), Reduced Glutathione (GSH), Super oxide dismutase (SOD) and Total protein levels were estimated from the liver tissue homogenate. The level of MDA (3.27Â±2.18) was significantly (pË0.001) increased whereas decreased level of total protein, GSH and SOD were found in CCl4 and paracetamol control group. Seven days extracts treatments restored these altered parameters in to normal where ethanol extract treatment group showed significant (pË0.001) result than aqueous extract. HPTLC study showed that presence of six phytoconstituents with corresponding Rf value. The study report concluded that M.reticulata has very good antioxidant effect against CCl4 and paracetamol induced liver damage with oxidative stress. Probable mechanism behind this protection against oxidative damage produced by CCl4 and paracetamol is its phytoconstiuents.